IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU (PPDB) SISTEM ZONASI SEKOLAH MENENGAH ATAS NEGERI DI JAKARTA TIMUR - Mu’allimah, Mu’allimah; Maesaroh, Maesaroh; Widowati, Nina (Journal of Public Policy and Management Review, 2024)
The New Student Admissions Policy (PPDB) in East Jakarta has used a zoning system as an effort to equalize access to education, bring students' residences closer to schools and eliminate the stigma of favorite schools. The implementation of this policy is based on Minister of Education and Culture Regulation Number 1 of 2021, however there are still obstacles in the policy implementation process. The aim of this research is to analyze the implementation of the PPDB policy for the State High School zoning system in East Jakarta and identify supporting and inhibiting factors for the implementation of this policy using the theory of public policy implementation according to Riant Nugroho and Van Meter and Van Horn. Data collection techniques were carried out using interviews, observation and literature studies through primary and secondary data sources as well as qualitative analysis. The results of this research show that policy implementation has been implemented but has not run optimally, as indicated by the existence of some people who choose schools based on the school's academic achievement, school reputation and school facilities. The supporting factors in implementing this policy are related to the policy targets, availability of resources, communication between organizations, characteristics of implementing agents and the attitudes of policy implementers. However, economic, social and political conditions in society as well as communication between organizations related to outreach activities to the community are still inhibiting factors in implementing this policy. Researchers recommend optimizing socialization to the community, continuing to strive to improve education by the local government together with schools in facilitating facilities and infrastructure, human resources and school management.